2013
DOI: 10.3389/fnbeh.2013.00207
|View full text |Cite
|
Sign up to set email alerts
|

Pleasant touch moderates the subjective but not objective aspects of body perception

Abstract: Un-myelinated C tactile afferents (CT afferents) are a key finding in affective touch. These fibers, which activate in response to a caress-like touch to hairy skin (CT afferents are not found in palm skin), may have more in common with interoceptive systems encoding body ownership, than afferent systems processing other tactile stimuli. We tested whether subjective embodiment of a rubber hand (measured through questionnaire items) was increased when tactile stimulation was applied to the back of the hand at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
67
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 55 publications
13
67
1
Order By: Relevance
“…This findings are still controversial, and further investigations of this measure and the physiological condition of participant's own arm are needed. Taken together, these results confirmed previous findings on the facilitatory role of affective touch in subjective ownership (Crucianelli et al, 2013;Lloyd et al, 2013;but see van Stralen et al, 2014, for proprioceptive drift effects). However, as stated in the introduction (see also Lloyd et al, 2013), it remains to be specified whether these effects are caused by bottom-up signals relating to the CT-system or by top-down factors such as learned expectations of sensory pleasure relating to the seen slow touch.…”
Section: Discussion Of Experiments 2 and General Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This findings are still controversial, and further investigations of this measure and the physiological condition of participant's own arm are needed. Taken together, these results confirmed previous findings on the facilitatory role of affective touch in subjective ownership (Crucianelli et al, 2013;Lloyd et al, 2013;but see van Stralen et al, 2014, for proprioceptive drift effects). However, as stated in the introduction (see also Lloyd et al, 2013), it remains to be specified whether these effects are caused by bottom-up signals relating to the CT-system or by top-down factors such as learned expectations of sensory pleasure relating to the seen slow touch.…”
Section: Discussion Of Experiments 2 and General Discussionsupporting
confidence: 82%
“…In particular, slow, caress-like touch that activates CT afferents optimally can enhance the experience of owning a rubber hand more than fast, emotionally neutral touch that does not cause optimal CT activation (Crucianelli, Metcalf, Fotopoulou & Jenkinson, 2013;Lloyd, Gillis, Lewis, Farrell & Morrison, 2013;van Stralen, van Zandvoort, Hoppenbrouwers, Vissers, Kappelle et al, 2014). Additionally, Lloyd and colleagues (2013) showed that slow/CT-optimal touch enhanced the subjective embodiment of the rubber hand also in the condition when touch was applied to glabrous (non-hairy) skin, known to lack CT afferents (Vallbo, Olausson & Wessberg, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…From these results, we speculate that there are different mechanisms for spatial updating and plastic changes in body ownership. In line with the speculation, proprioceptive drift arises even when participants do not feel ownership of the rubber hand (Holle et al, 2011; Rohde et al, 2011; Lloyd et al, 2013), although a subjective feeling of the illusion causes proprioceptive drift (Abdulkarim and Ehrsson, 2016). This suggests that oxytocin may modulate plastic changes in body ownership after visuotactile integration rather than during the visuotactile integration itself.…”
Section: Discussionmentioning
confidence: 72%
“…For example, recent studies have found that affective touch can modulate the sense of body ownership during the RHI. Specifically, slow, caress-like touch that is thought to be mediated by a specialized, interoceptive system (Löken, Wessberg, Morrison, McGlone, & Olausson, 2009) can increase subjective and objective measures of body ownership during the illusion more than fast, emotionally neutral touch (Crucianelli et al, 2013;Lloyd, Gillis, Lewis, Farrell, & Morrison, 2013;Löken et al, 2009;Moseley et al, 2008;Suzuki et al, 2013). Testing such multi-directional interactions between interoception and body ownership can thus shed further light into the neuroaffective components of functional motor disorders and related pathologies.…”
Section: Discussionmentioning
confidence: 96%